DEXTROMETHORPHAN TOXICITY IN PEDIATRIC AGE GROUP: A CASE SERIES (Journal of Forensic Medicine & Toxicology, 2023)
Dextromethorphan is a medication most often used as a cough suppressant (antitussive) in over-the-counter cough and cold medicines. It relieves the cough but does not treat the cause of the cough. Dextromethorphan works by decreasing activity in that part of the brain that causes coughing. It is sold in various forms like syrup, tablet and lozenge etc. Dextromethorphan comes alone and in combination with other drugs like antihistamines, cough suppressants and decongestants. (Used in Dry Cough). Dextromethorphan is basically in the morphinan class (Opioid) of medications with dissociative properties and also has stimulant properties at lower doses. It is advised that dextromethorphan should not be taken in more than the recommended amount, in a 24 –hour period. This can cause serious side effects or death in young children if taken in excess. Do not give the products containing dextromethorphan to children younger than 4 years of age. If you are giving these products to children aged between 4-11 years, use caution and follow the package directions carefully.
Keywords: Dextromethorphan; Toxicity; Pediatric age; Mohalla clinic